The Influence of Organizational Culture, Technology and Employee Qualifications on Company Performance in Oil & Gas Platform Fabrication in Batam - Indonesia - Purba, Laiden Ellenbin; Setyawan, Agustinus; Sudhartio, Lily (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research highlights the importance of the variable employee performance is influenced by organizational culture, technology and qualifications, and work motivation as a variable that mediates this relationship. Proving the findings demonstrated that company performance is significantly influenced by organizational culture, technology and employee qualifications. Evidence was also found that work motivation provides a mediating role that can help shape the influence of employee performance is influenced by organizational culture, technology and qualifications. The results obtained demonstrate that employee work motivation is an important factor that the Company must focus on to help improve employee performance at the Oil & Gas Platform Fabrication in Batam , Indonesia . Work motivation due to internal influences such as organizational culture and external influences such as the application of technology and increasing employee qualifications can improve the performance of each employee. These findings can certainly provide managerial implications for company management to continue to stimulate increased work motivation in each employee.